An efficient dynamic asymmetric catalytic system within a zinc-templated network12. Issue 55 (20th June 2019) - Serra-Pont, Anna; Alfonso, Ignacio; Solà, Jordi; Jimeno, Ciril
Abstract : Enhanced cooperativity leading to high catalytic activity and stereoselectivity in the direct aldol reaction has been achieved through a complex network of simple species interacting reversibly. Abstract : Enhanced cooperativity leading to high catalytic activity and stereoselectivity has been achieved through a complex network of simple species interacting reversibly. This novel dynamic catalytic system relies on bipyridine-based organocatalytic ligands and zinc(ii ) as the template. It demonstrates the effectiveness of dealing with mixtures rather than single species in asymmetric catalysis.